2020
DOI: 10.1088/2051-672x/ab70e8
|View full text |Cite
|
Sign up to set email alerts
|

Surfaces—topography and topology

Abstract: ISO 25178-2 specifies areal field parameters as well as areal feature parameters. While for the first group the whole set of points defining a scale-limited surface is considered, for the second group only a subset of surface features is taken into account. As a consequence, an adequate data structure for surface characterisation in combination with an appropriate method for surface simplification are required. Three data structures for surface characterisation, namely, Morse-Smale complexes, weighted surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 115 publications
0
12
0
Order By: Relevance
“…The watershed segmentation method is also suitable for analysis of additively manufactured freeform surfaces [199]. Other applications are presented in reviews [200][201][202]. However, Zabala et al [203] found a limited ability of the Spc parameter to characterise dental implant surfaces.…”
Section: Feature Parametersmentioning
confidence: 99%
“…The watershed segmentation method is also suitable for analysis of additively manufactured freeform surfaces [199]. Other applications are presented in reviews [200][201][202]. However, Zabala et al [203] found a limited ability of the Spc parameter to characterise dental implant surfaces.…”
Section: Feature Parametersmentioning
confidence: 99%
“…This method is based on the application of a watershed algorithm combined with an algorithm for simplifying the graph of relations between particular points. An algorithm called Wolf pruning, allows sub-patterns to be gathered into significant patterns [ 34 ]. This peak merging is obtained by applying a threshold to motif heights concerning a height threshold, which is usually specified as a percentage of the total height of the map.…”
Section: Resultsmentioning
confidence: 99%
“…DEM construction. DEM is based on the data source of the previously classified point cloud, corresponding to the terrain, using the topology in a metric space [50].…”
Section: Pix4dmapper Promentioning
confidence: 99%